Solid solution entropy metal ceramic material as well as preparation method and application thereof

Through solid-solution powder mix sintering technology, the problems of high cost and insufficient performance in the existing Ti(C,N)-based metal cermet preparation process are solved, and high-efficiency and low-cost preparation of Ti(C,N)-based metals with excellent performance are achieved. Ceramic materials expand their application areas.

CN119410991APending Publication Date: 2025-02-11ZHUZHOU HARD ALLOY GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411811860.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing Ti(C,N)-based cermet preparation process has problems such as high reaction temperature, high cost, low material strength and toughness, and high equipment requirements, which limits its engineering application and performance optimization.

Method used

The solid-solution powder mixture sintering technology is adopted to treat the composite powder by ball milling and drying to achieve one-time sintering to obtain solid-solution entropy metal cermet material, control the morphology and sintering technology of the raw material powder, and regulate the structure and performance of the material.

Benefits of technology

It has achieved high production efficiency and low production costs, and obtained Ti(C,N)-based cermet materials with dense tissue, small particle size, high hardness and good fracture toughness. It is suitable for high-end mold manufacturing and ultra-high temperature spraying and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410991A_ABST
    Figure CN119410991A_ABST
Patent Text Reader

Abstract

The invention discloses a solid solution entropy metal ceramic material as well as a preparation method and application thereof. The preparation method comprises the following steps: (1) preparing Ti (C, N) matrix powder, carbide additive phase powder and a metal binding phase to obtain composite powder; (2) the composite powder is sequentially subjected to ball milling and drying, and prefabricated powder is obtained; and (3) the prefabricated powder is sintered, and the solid solution entropy metal ceramic block material is obtained. According to the preparation method of the solid solution entropy metal ceramic material, grain size design and preparation can be conducted according to actual requirements, then the structure and performance of the metal ceramic material are regulated and controlled, the process is simple, the structure is controllable, operation is flexible, cost is low, and industrial application is facilitated; the solid solution entropy metal ceramic material has both hardness and fracture toughness, is excellent in performance, and is suitable for the industrial fields of high-end molds, sealing elements, high-temperature-resistant coatings and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cemented carbide, and in particular to a solid solution entropy metal ceramic material and a preparation method and application thereof. Background Art

[0002] Materials are the material basis for the survival and development of human society. The rapid development of science and technology has increased the demand for materials. Material scientists need to continuously design and develop new material systems with excellent performance to meet the requirements of various high-tech fields for materials. Ti (C, N)-based cermet is a non-oxide material with excellent performance and wide application. It has a series of advantages such as high melting point, high hardness, corrosion resistance, wear resistance, oxidation resistance, good electrical conductivity and thermal conductivity. Compared with traditional WC-Co cemented carbide, Ti (C, N)-based cermet has obvious advantages in processing finish and cutting speed. However, its density is only half of that of cemented carbide. It is gradually replacing the expensive WC-Co cemented carbide and has shown great application prospects in the fields of precision cutting tools, forming molds, seals, coatings, etc.

[0003] The existing Ti(C,N)-based cermet preparation process generally uses a carbon thermal reduction method to obtain a multi-component solid solution powder, and then the corresponding cermet bulk material can be obtained by using a spark plasma sintering technology, such as patent document CN113462944A, which discloses a boron-doped (Ti,Mo,W,Nb,Ta)(C,N)-Co-Ni powder, cermet and preparation method, but the reaction temperature of the process is 1300-1800 degrees Celsius, and the composite powder is sintered by SPS after being obtained, which increases the cost and also limits its engineering application to a certain extent. The phase purity obtained by this method cannot be guaranteed, the material strength and toughness are low, and the requirements for equipment are high, which will affect the engineering promotion and application of the material and technology. Therefore, the art urgently needs to design a new preparation technology to realize the dual control of the shape and property of the multi-component solid solution entropy Ti(C,N)-based cermet, obtain Ti(C,N)-based cermet with better performance, and further expand its application field. Summary of the invention

[0004] The present invention provides a solid solution entropy metal ceramic material with excellent performance, taking both hardness and fracture toughness into consideration, and a preparation method and application thereof, in order to solve the technical problems mentioned in the background technology.

[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for preparing a solid solution entropy metal ceramic material comprises the following steps: (1) Ti(C,N) matrix powder, carbide additive phase powder and metal binder phase are configured according to a set ratio to obtain composite powder; (2) ball milling and drying the composite powder in sequence to obtain a prefabricated powder; (3) Sintering the prefabricated powder to obtain the solid solution entropy metal ceramic material.

[0006] The present invention adopts solid solution powder for mixed sintering, and solid solution entropy metal ceramic material can be obtained by only one sintering, which has high production efficiency and low production cost, and avoids the existing technology of using carbon thermal reduction to obtain solid solution powder and the inability to ensure the phase purity of the product during the nitriding process, which leads to adverse effects on the material structure and performance.

[0007] As a further preferred embodiment of the above technical solution, in step (3), the specific operation of sintering the prefabricated powder is as follows: heating the prefabricated powder to 1000-1100°C and keeping the temperature for 30-60 minutes to facilitate the full completion of the liquid phase sintering of the bonding phase during the metal ceramic sintering process; then heating the prefabricated powder to 1450-1490°C in a second stage and keeping the temperature for 90-180 minutes; while heating the prefabricated powder in the second stage, nitrogen is charged for pressurization, and after the second stage of heating is completed, nitrogen is stopped and switched to argon, and the pressure is increased to a set pressure for pressure maintenance, and after the insulation is completed, the pressure is evenly reduced to zero, thereby completing the complete densification of the metal ceramic powder and obtaining the solid solution entropy metal ceramic block with a single phase. During the sintering process, 1000~1100℃ is an important phase change temperature range. Starting to fill with nitrogen at this time can avoid the occurrence of denitrification in the material. Stopping the filling of nitrogen in the insulation section is mainly because the phase change behavior in the material has been completed when entering the insulation section. Insulation sintering is mainly to increase its density. If nitrogen is filled at this time, it may cause the nitrogen content in the material to increase, and nitrogen increase behavior will also have a negative impact on the material performance.

[0008] As a further preferred embodiment of the above technical solution, the heating rate of the first stage of heating is 5-15°C / min, and the heating rate of the second stage of heating is 3-5°C / min.

[0009] As a further preferred embodiment of the above technical solution, after the insulation is completed, the pressure is evenly reduced to zero within 30 minutes.

[0010] As a further preferred embodiment of the above technical solution, the Ti(C,N) matrix powder is mainly Ti(C 0.5 N 0.5) metal ceramic powder, the particle size of the Ti(C,N) matrix powder is 0.4~0.7μm, the carbide additive phase powder is a hard phase powder in the form of a solid solution composed of (Ti,W,Mo)C and (Nb,Ta)C; the metal bonding phase includes at least two of Fe, Co, Ni and Cu. The additive phase is added in the form of a solid solution, and decarburization is not easy to occur during long-term pressure-holding sintering. The limitation on the particle size of the matrix powder is designed based on the Kirkendall effect principle and the material design concept. In the design process of the material powder system, the hardness and toughness of the material are improved by reducing the particle size of the matrix powder, so that a new metal ceramic material with excellent strength and toughness can be obtained.

[0011] As a further preferred embodiment of the above technical solution, the mass ratio of the Ti(C,N) matrix powder, the carbide additive phase powder and the metal binder phase is (4.5-6): (2-3): (1-3.5), and further preferably is (5-5.5): (2.5-3): (2-3).

[0012] As a further preferred embodiment of the above technical solution, the metal bonding phase includes Co and Ni, and the content of Co is greater than that of Ni. The above bonding phase can better improve the material properties.

[0013] As a further preferred embodiment of the above technical solution, in step (2), the ball milling operation adopts a wet mixing ball milling process, the ball milling medium is anhydrous ethanol, the ball mill speed is 10-50 r / min, the ball to material ratio is (2-10):1, and more preferably the ball mill speed is 20-30 r / min, and the ball to material ratio is (5-8):1; the drying operation adopts vacuum drying, the drying temperature is 50-80°C, and after drying, a 200-300 mesh sieve is used for sieving and granulating to obtain the prefabricated powder, and more preferably the drying temperature is 70-80°C, and after drying, a 200 mesh sieve is used for sieving and granulating.

[0014] Based on the same technical concept, the present invention also provides a solid solution entropy metal ceramic material prepared by the preparation method of the above technical solution. The metal ceramic material has a core ring structure, including a hard phase as a core, a solid solution phase as a ring structure, and a bonding phase.

[0015] As a further preferred embodiment of the above technical solution, the particle size of the core ring structure is submicron level.

[0016] Based on the same technical concept, the present invention also provides an application of the solid solution entropy metal ceramic material of the above technical solution, the solid solution entropy metal ceramic block material is used to manufacture molds, cutting tools, and seals; or the solid solution entropy metal ceramic block is crushed to obtain powder and then used in the field of high temperature resistant coatings. The present invention has the following beneficial effects: (1) The method for preparing solid solution entropy metal ceramic materials of the present invention prepares metal ceramics by controlling the raw material powder morphology and sintering technology. The grain size can be designed and prepared according to actual needs, thereby regulating the synergistic effect of its structure and performance. The process is simple, the structure is controllable, the operation is flexible, the cost is low, and it is easy to industrialize and apply; (2) This invention realizes the dual control of shape and properties of solid solution entropy metal ceramic materials through composite powder co-sintering technology. The ceramic material produced has dense structure, small particle size, uniform distribution of hard phase and bonding phase, and fully considers the influence of hard phase on hardness and the influence of bonding phase distribution on material toughness, achieving a balance between hardness and fracture toughness. The product has excellent performance and is suitable for industrial fields such as high-end mold manufacturing and ultra-high temperature spraying.

[0017] The present invention will be further described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 The present invention is a flow chart of the preparation method of the solid solution entropy metal ceramic material.

[0019] Figure 2 This is the microstructure morphology of the metal ceramic material obtained in Example 1 of the present invention.

[0020] Figure 3 This is the XRD result of the phase distribution of the metal ceramic material obtained in Example 1 of the present invention.

[0021] Figure 4 This is the microstructure morphology of the metal ceramic material obtained in Example 2 of the present invention.

[0022] Figure 5 This is the microstructure morphology of the metal ceramic material obtained in Example 5 of the present invention.

[0023] Figure 6 This is the microstructure morphology of the metal ceramic material obtained in Example 6 of the present invention.

[0024] Figure 7 This is the microstructure morphology of the metal ceramic material obtained in Comparative Example 1 of the present invention.

[0025] Figure 8 This is the XRD result of the phase distribution of the metal ceramic material obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, but the present invention can be implemented in many different ways as defined and covered by the claims.

[0027] Embodiment 1: like Figure 1 As shown, the preparation method of the solid solution entropy metal ceramic material of this embodiment includes the following steps: (1) Using Ti(C,N) powder, carbide solid solution powder and metal binder phase as raw materials, prepare composite powder according to the component system in Table 1 and the mass ratio; Among them, Ti(C,N) powder is a hard phase, which is Ti(C 0.5 N 0.5 ) Metal ceramic powder, carbon-nitrogen ratio is 5:5, particle size is about 0.6 μm; The solid solution powders are (Ti, W, Mo) C and (Nb, Ta) C, and the particle size is about 1 μm; The metal binder phase is Co and Ni, with a particle size of about 1 μm; Table 1: Specific ingredients and contents of raw materials in Example 1

[0028] (2) using anhydrous ethanol as a ball milling medium to wet-mix the composite powder, the ball mill speed is 30 r / min, the ball milling is performed for 48 hours, and the composite powder is dried at 80° C. in a vacuum drying oven, and then sieved and granulated on a 200-mesh sieve to obtain a prefabricated powder; (3) The prefabricated powder is loaded into a mold, and the temperature is increased to 1100°C in a hot pressing furnace at a heating rate of 10°C / min and then kept at this temperature for 60 min. The temperature is then increased to 1450°C in a second stage at a heating rate of 5°C / min. Nitrogen is introduced to pressurize the sample during the second stage of heating. When the second stage of heating is completed, the nitrogen is stopped and switched to argon. The pressure is increased to a maximum value (10-20 MPa) and maintained. After the holding time of 120 min, the pressure is evenly reduced. After 30 min, the external pressure is unloaded to zero, and the sample is naturally cooled in the furnace to obtain a ceramic block.

[0029] The solid solution entropy metal ceramic material of this embodiment is prepared by the preparation method of this embodiment, and has a core ring structure, including a hard phase as a core, a solid solution phase as a ring structure, and a bonding phase.

[0030] The structure and performance of the solid solution entropy metal ceramic material of this embodiment are measured, and the microstructure morphology is as follows: Figure 2 The XRD results of phase distribution are shown in Figure 3 As shown, the material density is 7.26g / cm 3 The material hardness is 92.6HRA and the fracture toughness is 8.74MPa·m1 / 2 .

[0031] Depend on Figure 2 It can be seen that the material prepared in this embodiment has a classic core ring structure (the size of the core ring structure is submicron and has good uniformity), a good coating effect, and a uniform distribution of the gray solid solution phase with a high content. Figure 3 From the XRD results, it can be seen that the physical phases of the final material are mainly solid solution phase (Ti, M) (C, N) (where M = Ti, W, Mo, Nb, Ta) and bonding phase Co + Ni, and the purity of the material is relatively high.

[0032] Embodiment 2: The preparation method of the solid solution entropy metal ceramic material of this embodiment is consistent with that of Example 1 in other conditions, and the only difference is that in step (3) of this embodiment, the temperature is raised to 1470°C in the second stage.

[0033] The solid solution entropy metal ceramic material of this embodiment is prepared by the preparation method of this embodiment, and has a core ring structure, including a hard phase as a core, a solid solution phase as a ring structure, and a bonding phase. The microstructure morphology is as follows: Figure 4 As shown, the density of the obtained Ti(C,N) based cermet material is 7.31 g / cm 3 The material hardness is 92.5HRA and the fracture toughness is 8.97MPa·m 1 / 2 .

[0034] Depend on Figure 4 It can be seen that the material prepared in this embodiment has a classic core ring structure (the size of the core ring structure is submicron and has good uniformity), the coating effect is good, and the gray solid solution phase is evenly distributed and has a high content.

[0035] At the same time, the block obtained in this embodiment was crushed into powder and sprayed onto the surface of a Q235 steel substrate to successfully prepare a metal-ceramic composite coating with a dense structure and good metallurgical bonding with the substrate. The hardness of the near-surface layer was as high as 1200HV1, which is about 3 times that of the substrate, and can significantly improve the wear resistance of the substrate material.

[0036] Embodiment 3: The preparation method of the solid solution entropy metal ceramic material of this embodiment is consistent with that of Example 1 in other conditions, and the only difference is that the holding time after the second stage of heating in step (3) of this embodiment is 150 minutes.

[0037] The solid solution entropy metal ceramic material of this embodiment is prepared by the preparation method of this embodiment, and has a core ring structure, including a hard phase as a core, a solid solution phase as a ring structure, and a bonding phase. The material density is 7.29g / cm 3, the material hardness is 92.4HRA, and the fracture toughness is 9.02MPa·m 1 / 2 .

[0038] Embodiment 4: The preparation method of the solid solution entropy metal ceramic material of this embodiment is consistent with that of Example 1 in other conditions, except that the binding phase in step (1) of this embodiment is Co, Ni and Fe, and the content of the three metals is 5%.

[0039] The solid solution entropy metal ceramic material of this embodiment is prepared by the preparation method of this embodiment, and has a core ring structure, including a hard phase as a core, a solid solution phase as a ring structure, and a bonding phase. The material density is 7.29g / cm 3 , the material hardness is 92.5HRA, and the fracture toughness is 8.86MPa·m 1 / 2 .

[0040] Embodiment 5: The preparation method of the solid solution entropy metal ceramic material of this embodiment is consistent with that of Example 1 in other conditions, and the only difference is that in step (3) of this embodiment, the temperature is raised to 1490° C. in the second stage.

[0041] The solid solution entropy metal ceramic material of this embodiment is prepared by the preparation method of this embodiment, and has a core ring structure, including a hard phase as a core, a solid solution phase as a ring structure, and a bonding phase. The microstructure morphology is as follows: Figure 5 As shown, the material density is 7.29g / cm 3 , the material hardness is 92.3HRA, and the fracture toughness is 8.69MPa·m 1 / 2 .

[0042] Depend on Figure 5 It can be seen that the material prepared in this embodiment has a classic core ring structure (the size of the core ring structure is submicron and has good uniformity), the coating effect is good, and the gray solid solution phase is evenly distributed and has a high content. The high-temperature sintering results in a relatively large grain size.

[0043] Embodiment 6: The preparation method of the solid solution entropy metal ceramic material of this embodiment is consistent with that of Example 1 in other conditions, and the only difference is that the raw materials of this embodiment are different from those of Example 1. The raw materials of this embodiment are shown in Table 2.

[0044] The solid solution entropy metal ceramic material of this embodiment is prepared by the preparation method of this embodiment, and has a core ring structure (the size of the core ring structure is submicron and has good uniformity), including a hard phase as a core, a solid solution phase as a ring structure, and a bonding phase. The microstructure morphology is as follows: Figure 6 As shown, the material density is 7.18g / cm 3The material hardness is 91.8HRA and the fracture toughness is 9.76MPa·m 1 / 2 .

[0045] Table 2: Specific ingredients and contents of raw materials in Example 6

[0046] Depend on Figure 6 It can be seen that the material prepared in this embodiment has a classic core ring structure and a good coating effect. At the same time, the gray solid solution phase is evenly distributed and has a higher content than that in the previous embodiments.

[0047] Embodiment 7: The preparation method of the solid solution entropy metal ceramic material of this embodiment is consistent with that of Example 6 in other conditions, and the only difference is that in step (3) of this embodiment, the temperature is raised to 1490°C in the second stage.

[0048] The solid solution entropy metal ceramic material of this embodiment is prepared by the preparation method of this embodiment, and has a core ring structure, including a hard phase as a core, a solid solution phase as a ring structure, and a bonding phase. The material density is 7.23g / cm 3 The material hardness is 92.1HRA and the fracture toughness is 9.58MPa·m 1 / 2 .

[0049] Comparative Example 1: The preparation method of the solid solution entropy metal ceramic material in this comparative example is consistent with Example 1 in other conditions, and the only difference is that in step (3) of this comparative example, the temperature is raised to 1410°C in the second stage.

[0050] The density of the metal ceramic material obtained in this comparative example is 7.12 g / cm 3 , material hardness is 91.3HRA, fracture toughness is 7.12MPa*m 1 / 2 The microstructure morphology is as follows Figure 7 The XRD results of phase distribution are shown in Figure 8 shown.

[0051] Depend on Figure 7 It can be seen that the core ring structure of the material obtained in the comparative example of the present invention is not obvious, and there are obvious holes. Figure 8 The XRD results show that in addition to the solid solution phase and the bonding phase, there are also carbides that have not been completely decomposed into solid solution in the final material.

[0052] Comparative Example 2: The preparation method of the solid solution entropy metal ceramic material in this comparative example is consistent with Example 1 in other conditions, with the only difference being that no carbide solid solution powder is added to the raw materials in this comparative example, but an equal amount of carbide is added in the same proportion.

[0053] The density of the metal ceramic material obtained in this comparative example is 7.27 g / cm 3 , material hardness is 92.3HRA, fracture toughness is 7.96MPa*m 1 / 2 , the toughness of the obtained ceramic material is relatively low.

[0054] The above are only preferred embodiments of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.

[0055] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a solid solution entropy metal ceramic material, characterized in that: The following steps are involved: (1) Ti(C,N) matrix powder, carbide additive phase powder and metal binder phase are configured according to a set ratio to obtain composite powder; (2) ball milling and drying the composite powder in sequence to obtain a prefabricated powder; (3) Sintering the prefabricated powder to obtain the solid solution entropy metal ceramic material.

2. The method for preparing a solid solution entropy metal ceramic material according to claim 1, characterized in that: In step (3), the specific operation of sintering the prefabricated powder is as follows: heating the prefabricated powder to 1000-1100°C and keeping it warm for 30-60 minutes to facilitate the full completion of the liquid phase sintering of the binding phase during the metal ceramic sintering process; then heating the prefabricated powder to 1450-1490°C in a second stage and keeping it warm for 90-180 minutes; while heating the prefabricated powder in the second stage, nitrogen is charged to increase the pressure, and after the second stage of heating is completed, nitrogen is stopped and switched to argon, and the pressure is increased to a set pressure for pressure maintenance. After the insulation is completed, the pressure is evenly reduced to zero, and the metal ceramic powder is completely densified, that is, the solid solution entropy metal ceramic block with a single phase is obtained.

3. The method for preparing a solid solution entropy metal ceramic material according to claim 2, characterized in that: The heating rate of the first stage heating is 5-15°C / min, and the heating rate of the second stage heating is 3-5°C / min.

4. The method for preparing a solid solution entropy metal ceramic material according to claim 2, characterized in that: After the insulation is completed, the pressure is evenly reduced to zero within 30 minutes.

5. The method for preparing a solid solution entropy metal ceramic material according to claim 1, characterized in that: The Ti(C,N) matrix powder is mainly Ti(C 0.5 N 0.5 ) metal ceramic powder, the particle size of the Ti(C,N) matrix powder is 0.4~0.7μm, the carbide added phase powder is a hard phase powder in the form of a solid solution composed of (Ti,W,Mo)C and (Nb,Ta)C; the metal bonding phase includes at least two of Fe, Co, Ni and Cu.

6. The method for preparing a solid solution entropy metal ceramic material according to claim 5, characterized in that: The mass ratio of the Ti(C,N) matrix powder, the carbide additive phase powder and the metal bonding phase is (4.5-6): (2-3): (1-3.5).

7. The method for preparing a solid solution entropy metal ceramic material according to claim 6, characterized in that: The mass ratio of the Ti(C,N) matrix powder, the carbide additive phase powder and the metal bonding phase is (5-5.5): (2.5-3): (2-3).

8. The method for preparing a solid solution entropy metal ceramic material according to claim 5, characterized in that: The metal bonding phase includes Co and Ni, and the content of Co is greater than that of Ni.

9. The method for preparing a solid solution entropy metal ceramic material according to any one of claims 1 to 8, characterized in that: In step (2), the ball milling operation adopts a wet mixing ball milling process, the ball milling medium is anhydrous ethanol, the ball mill speed is 10-50 r / min, and the ball-to-material ratio is (2-10):1; the drying operation adopts vacuum drying, the drying temperature is 50-90°C, and after drying, a 200-300 mesh sieve is used for screening and granulation to obtain the prefabricated powder.

10. The method for preparing a solid solution entropy metal ceramic material according to claim 9, characterized in that: The ball mill speed is 20-30 r / min, and the ball-to-material ratio is (5-8):1; the drying operation adopts vacuum drying, the drying temperature is 70-80°C, and after drying, a 200-mesh screen is used for screening and granulation.

11. A solid solution entropy metal ceramic material obtained by the preparation method according to any one of claims 1 to 10, characterized in that: The solid solution entropy metal ceramic material is in a core ring structure, including a hard phase as a core, a solid solution phase as a ring structure, and a bonding phase.

12. The solid solution entropy metal ceramic material according to claim 11, characterized in that: The particle size of the core ring structure is submicron level.

13. An application of the solid solution entropy metal ceramic material according to claim 11 or 12 or the solid solution entropy metal ceramic material prepared by the preparation method according to any one of claims 1 to 10, characterized in that: The solid solution entropy metal ceramic block material is used to manufacture molds, cutting tools, and seals; or the solid solution entropy metal ceramic block is crushed into powder and used in the field of high temperature resistant coatings.

Citation Information

Patent Citations

  • Boron-doped (Ti, W, Mo, Nb, Ta) (C, N)-Co-Ni powder, metal ceramic and preparation method

    CN113462944A